Lithostructural Control in the Development of Potholes in the Rock Bed of the Carnaúba River, Seridó Geopark, NE Brazil - Dias, João Rafael Vieira; Cordeiro, Abner Monteiro Nunes; Bastos, Frederico de Holanda; Maia, Rubson Pinheiro; Nascimento, Marcos Antônio Leite do (Revista Brasileira de Geomorfologia, 2024)
Granitic forms resulting from turbulent flow, with hydraulic vortices, characterize the rocky bed of the lower course of the Carnaúba River, in a geosite of the Seridó Geopark, in the Seridó Oriental microregion, Northeast Brazil. These forms constitute a variety of types of potholes that individually represent various stages of evolution, in addition to reflecting the variation in the erosive potential of river flow throughout the Quaternary. From a bibliographical review, fieldwork (quantification and measurements of the potholes), high-resolution photogrammetry and morphostructural analysis of the generated cartographic products, it was possible to establish a correlation between the preferential orientation of the potholes and the direction of the planes of weakness, as well as the classification of potholes by morphometric parameters. In this work it was demonstrated that the efficiency of hydraulic vortices is associated with discontinuity structures and the mineralogical composition of granite facies, with abrasive erosion being responsible for sculpting potholes, with different dimensions and geometries. In the rocky bed of the Carnaúba River, the small potholes deepen and their diameter evolves into cylindrical shapes as the turbulent vertical flow increases, eventually becoming sigmoidal. The lateral potholes, located on the walls of the river channel, are deeper than they are wide, and represent a destructive phase of evolution.